Tensorial theory of relativistic quantum mechanics in 1+1 dimensions - Alonso, Vidal; De Vincenzo, Salvatore; Mondino, Luigi (Ciencia)
The relativistic quantum mechanical tensorial theory in 1 + 1 dimensions is considered. Its kinematical and dynamical features are reviewed as well as the problem of finding the Dirac spinor for given finite multivectors. For stationary states, the dynamical tensorial equations, equivalent to the Dirac equation, are solved for a free particle and for a particle inside a box.